8A.04: RISK OF MORTALITY IN RELATION TO AN UPDATED CLASSIFICATION OF LEFT VENTRICULAR GEOMETRIC ABNORMALITIES IN A GENERAL POPULATION. (June 2015) - Cuspidi, C.; Facchetti, R.; Bombelli, M.; Sala, C.; Tadic, M.; Grassi, G.; Mancia, G.
Abstract : Objective: We estimated the risk of cardiovascular and all-cause mortality associated with left ventricular (LV) geometric patterns, as defined by a new classification system proposed by the Dallas Heart Study, in 1716 representatives of the general population of Monza enrolled in the Pressioni Monitorate e Loro Associazioni (PAMELA) study. Design and method: Cut-points for abnormal LV geometric patterns were derived from reference values of the healthy fraction of the PAMELA population by combining LV mass (LVM) index, LV diameter and relative wall thickness. Death certificates were collected over an average 211 months follow-up period. Results: During follow-up, 89 fatal cardiovascular events and 264 all-cause deaths were recorded. Concentric remodeling (CR) was the most common LV geometric abnormality (9.4%) followed by eccentric non-dilated LVH (6.3%), concentric LVH (4.6%) and dilated LVH (3.5%). Compared to normal LV geometry, concentric LVH (HR = 4.04, 95% CI: 2.05–7.97, p < 0.0001), dilated LVH (HR = 3.83, 95% CI: 1.93–7.60, p = 0.0001) and eccentric non-dilated LVH (HR = 2.61, 95% CI: 1.39–4.92, p = 0.003) predicted the risk of cardiovascular mortality, after adjustment for baseline covariates, including ambulatory blood pressure. Similar findings were observed for all-cause mortality. Only concentric LVH maintained a significant prognostic value for both outcomes after adjustment for baseline differences in LVM index. Conclusions: The new classification system of LV geometric patterns, may improve mortality risk stratification in a general population. The risk is markedly dependent on LVM values; only concentric LVH provides a prognostic information beyond that conveyed by cardiac mass.